Advances in genetics. - Friedmann, Theodore; Dunlap, Jay C.; Goodwin, Stephen F. (Advances in genetics, 2014)
The field of genetics is rapidly evolving, and new medical breakthroughs are occurring as a result of advances in our knowledge of genetics. Advances in Genetics continually publishes important reviews of the broadest interest to geneticists and their colleagues in affiliated disciplines. Volume 85 presents an eclectic mix of articles of use to all human and molecular geneticists on topics including: association mapping in crop plants; miRNA-mediated crosstalk between transcripts; unisexual reproduction; and more.